Tooth Extraction Management Using the Open Method Extraction Technique for the Maxillary First Molar - Ni Luh Sudiasih; Ni Putu Dian Cipta Dewi (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Extraction is the act of extracting teeth and tooth roots from sockets involving bone tissue and soft tissue in the oral cavity. The ideal tooth extraction is the extraction of an intact tooth or root without causing pain. There are two types of tooth extraction techniques in dentistry, namely the open method and the closed method. Tooth extraction with the open method technique is carried out because many parts of the crown structure are missing, so that the tooth cannot be held using pliers or other instruments, which makes it difficult for the tooth to be extracted. In young patients with cases of buried root residual teeth, extraction can be done using the open method technique. Case: A 47-year-old female patient came to RSGM Saraswati Denpasar with a complaint that her upper right jaw tooth only had a root left and wanted to be extracted immediately, and wanted to have a denture. Objective examination of the patient's physical condition is good, with blood pressure 125/88 mmHg. Intraoral examination showed that there were remaining roots 16. Radiographic examination found the remaining roots from tooth 16, which were clinically invisible. Case Management: Case management with extractions of teeth 16 with local anesthesia, accompanied by alveoloplasty, was performed in the Minor Oral Surgery Unit of Saraswati Dental Hospital, Denpasar. Conclusion: Minor surgical treatment in hypertensive patients can be done by considering the patient's medical history, so it can ensure the right modification for safe tooth extraction.